The effect of mineral fertilizers on the economic efficiency of winter wheat production in the direct sowing technology in the Stavropol territory - N. N. Shapovalova; L. R. Oganyan; А. А. Voropaeva (Зерновое хозяйство России)
Direct sowing of crops reduces the cost of soil cultivation for farmers, but significantly increases the cost of fertilizers, pesticides and new agricultural equipment. The problem of the economic feasibility of introducing increased doses of mineral fertilizers when sowing winter wheat and carrying out nitrogen fertilization in the no-till technology is of great relevance, but has been little studied. The purpose of the current study was to estimate the economic efficiency of winter wheat grain production in the direct sowing (no-till) technology with different methods and doses of mineral fertilizers in conditions of unstable moisture in the Stavropol Territory. The study was carried out in the trial on the fields of the North-Caucasus Federal Research Agricultural Center in 2017–2019. The variants for using fertilizers when sowing winter wheat were as follows: without fertilizers; with N6 Р26; with N12Р52; with N24Р104; with N52Р52; with N52Р52K52; with N52; with N104Р52K52. In the early spring period, on the background of fertilizers used when sowing the crop, there was carried out additional fertilizing with ammonium nitrate at a dose of N52. There was found that all doses of mineral fertilizers used when sowing winter wheat, reduced the unit cost of production on 1.8–19.8%, raised profits on 24.8–177.1% and improved profitability on 2.5–43.1%. The best economic indicators were established when using N52 and N104Р52К52, at which there was obtained the minimum cost price of 1 ton of grain (6216–6494 rubles), the highest profitability (77.1–85.0%) and profit (27 830–33 454 rubles/ha). Early spring additional fertilizing (N52) of winter wheat on the background of fertilizers used when sowing the crop after peas turned out to be an ineffective agrochemical method. As a result, the cost price of a production unit increased on 0.5–23.4%, and the level of production profitability reduced on 0.8–35.0%. In no-till technology, the use of higher doses of nitrogen fertilizers during winter wheat sowing provided not only a significant increase of grain productivity and quality, but also maximum economic benefits.